iNOS Inhibition Reduces Lung Mechanical Alterations and Remodeling Induced by Particulate Matter in Mice - Prado, Carla Máximo; Righetti, Renato Fraga; Lopes, Fernanda Degobbi Tenorio Quirino dos Santos; Leick, Edna Aparecida; Arantes-Costa, Fernanda Magalhães; de Almeida, Francine Maria; Saldiva, Paulo Hilário Nascimento; Mauad, Thais; Tibério, Iolanda de Fátima Lopes Calvo; Martins, Mílton de Arruda (Pulmonary Medicine, 2019)
Background. The epidemiologic association between pulmonary exposure to ambient particulate matter (PM) and acute lung damage is well known. However, the mechanism involved in the effects of repeated exposures of PM in the lung injury is poorly documented. This study tested the hypotheses that chronic nasal instillation of residual oil fly ash (ROFA) induced not only distal lung and airway inflammation but also remodeling. In addition, we evaluated the effects of inducible nitric oxide inhibition in these responses. For this purpose, airway and lung parenchyma were evaluated by quantitative analysis of collagen and elastic fibers, immunohistochemistry for macrophages, neutrophils, inducible nitric oxide synthase (iNOS), neuronal nitric oxide synthase (nNOS), and alveolar septa 8-iso prostaglandin F2α (8-iso-PGF-2α) detection. Anesthetized in vivo (airway resistance, elastance, H, G, and Raw) respiratory mechanics were also analyzed. C57BL6 mice received daily 60ul of ROFA (intranasal) for five (ROFA-5d) or fifteen days (ROFA-15d). Controls have received saline (SAL). Part of the animals has received 1400W (SAL+1400W and ROFA-15d+1400W), an iNOS inhibitor, for four days before the end of the protocol. A marked neutrophil and macrophage infiltration and an increase in the iNOS, nNOS, and 8-iso-PGF2 α expression was observed in peribronchiolar and alveolar wall both in ROFA-5d and in ROFA-15d groups. There was an increment of the collagen and elastic fibers in alveolar and airway walls in ROFA-15d group. The iNOS inhibition reduced all alterations induced by ROFA, except for the 8-iso-PGF2 α expression. In conclusion, repeated particulate matter exposures induce extracellular matrix remodeling of airway and alveolar walls, which could contribute to the pulmonary mechanical changes observed. The mechanism involved is, at least, dependent on the inducible nitric oxide activation.